Sustainable Chromium Recovery From Wastewater Using Mango and Jackfruit Seed Kernel Bio-Adsorbents - Giri, Deen Dayal; Shah, Maulin; Srivastava, Neha; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Pal, Dan Bahadur (Frontiers in Microbiology, 2021)
Wastewater is a rich source of valuable chemicals of industrial importance. . However, their economic recovery is crucial for sustainability. The objective of present work is recovered hexavalent Chromium (Cr VI) as a value-added transition metal from wastewater cost-effectively, the biosorbent derived from seed kernel of Mango seed kernel (M) and Jack fruit (JF) were applied for the removing the metal from simulated wastewater. The Functional groups of the biomass was analysed with the help of Fourier transform Infrared Spectroscopy, micrographs were generated using Scanning Electron Microscope, and crystallinity was determined by X-ray diffractometer. The concentration of Cr VI in wastewater analysed by inductively coupled plasma optical emissions spectrometer. Process parameters (pH, dose, contact time, temperature, and initial concentration) were optimized for efficient Cr VI adsorption was by response surface methodology-based Box-Behnken design employing Design-software 6.0.8. The batch experiment at room temperature at pH 4.8, Cr VI removal ~94 % (M) and ~92 %(JF) were achieved by using dose 60mg and initial Cr (VI) concentration 2ppm in 120 min. The equilibrium Cr binding on the biosorbent was well explained using Freundlich isotherm (R2 = 0.97) indicated the indirect interactions between Cr (VI) and the biosorbent. Biosorption of Cr (VI) followed the pseudo-order and intra-particle diffusion models. The maximum adsorption capacity of M and JF bio-adsorbent is 517.24g/mg and 207.6 g/mg respectively. These efficient, cost effective and eco-friendly biosorbent could be potentially applied for removing toxic Cr (VI) from polluted water.